2017
DOI: 10.1016/j.nano.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle delivery of chemotherapy combination regimen improves the therapeutic efficacy in mouse models of lung cancer

Abstract: The combination chemotherapy regimen of cisplatin (CP) and docetaxel (DTX) is effective against a variety of cancers. However, combination therapies present unique challenges that can complicate clinical application, such as increases in toxicity and imprecise exposure of tumors to specific drug ratios that can produce treatment resistance. Drug co-encapsulation within a single nanoparticle (NP) formulation can overcome these challenges and further improve combinations’ therapeutic index. In this report, we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The herein reported drug loadings are, to the best of our knowledge, unprecedented for other PM containing two different drugs. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The herein reported drug loadings are, to the best of our knowledge, unprecedented for other PM containing two different drugs. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Other similar systems based on different cationic blocks (such as polyethyleneimine, polylysine and dendrimer) and hydrophobic copolymers were also synthesized for combination delivery of hydrophobic drugs and nucleic acids [147]. Further, Wang et al developed a cationic core shell nanoparticle system using biodegradable amphiphilic copolymers for DNA/siRNA and PTX co-delivery [127]. The polymer namely, poly (N-methyldietheneamine sebacate)-co-((cholesteryl oxocaronylamidoethyl) methyl bis(ethylene) ammonium bromide) sebacate formed self assembling core–shell NPs encapsulating the drug and gene payload.…”
Section: Combination Of Sirna/chemodrugs In a Single Carriermentioning
confidence: 99%
“…The polymer namely, poly (N-methyldietheneamine sebacate)-co-((cholesteryl oxocaronylamidoethyl) methyl bis(ethylene) ammonium bromide) sebacate formed self assembling core–shell NPs encapsulating the drug and gene payload. These core–shell NPs demonstrated superior tumor suppression both in the in vitro cell cultures and in vivo animal models [127]. Natural polymers such as dextran, chitosan, gelatin and hyaluronic acid have several advantages compared to synthetic polymers in terms of biological safety of the engineered nano-constructs.…”
Section: Combination Of Sirna/chemodrugs In a Single Carriermentioning
confidence: 99%
“…Another study reported that the dual drugs loading in single nanoparticle could be significantly improved in view of its therapeutic index of that free CDDP against a lung cancer model. These CDDP loaded PLGA NPs induced apoptosis by developing irreversible DNA crosslinking and DOX stabilized the microtubules network by blocking the mitotic cell division [28]. Cisplatin-loaded folic acid-poly(lactic-co-glycolic acid) (PLGA) PNPs were prepared through W/O/W double-emulsion solvent evaporation method having the size of between 150 and 250 nm.…”
Section: Polylactic-co-glycolic Acid Nanoparticlesmentioning
confidence: 99%